TRUST: Transportation and Road Monitoring System for Ubiquitous Real-Time Information Services - Almeida, João Miguel Pereira (2020)
This paper presents the main design decisions and the architecture layout of TRUST project. The main goal of the project is to develop a weather monitoring system for road infrastructures, in order to identify potential hazards for driving and the consequent generation of alerts and recommendations for vehicle users and traffic management centers. Hybrid vehicular communications (3G/4G + ETSI ITS-G5) among vehicles, roadside infrastructure and cloud servers are employed with the aim of collecting sensor information and disseminating warning messages to the drivers in risky locations (e.g. aquaplaning, fog, floods), thus reducing the number of accidents and associated fatalities. The three layers of the system (sensor, communications and information) are described in detail, together with the applications and services that the project will deploy.